OnlyFans’ sexual content policy - Robson, Karen, (SAGE Business cases., 2021)
Within the span of one week, social network OnlyFans announced a policy which would ban users from sharing sexually explicit content and then reversed this decision. The reversal of this policy came after backlash from users, including online sex workers and their customers. This case covers the OnlyFans business, its initial decision to ban sexually explicit content, and the subsequent reversal of this decision. Students are asked to consider how OnlyFans is positioned as a social network, the reasons why OnlyFans initially decided to ban this type of content, and to determine whether the initial policy announcement or its reversal was a mistake.